(untitled) (Docentes 2.0 Journal, 2024)
Digital services are globalizing services without time and space limits that reduce costs by guaranteeing timely attention through the Internet and social networks. The objective of the research was to analyze the experiences of digital services in document management. The hermeneutic method was used as a phenomenological paradigm with a qualitative approach, a phenomenological design, and an interpretive cross-section type. The sample consisted of 5 key users. The data was collected using the semi-structured interview guide instrument. Then, the thematic and hermeneutic analysis of the experiences collected was carried out according to the categories of digital service and document management in the Peruvian educational context. The results reveal a duality in the experiences of the users. Some perceive improvements in document management through digital technologies, while others highlight the lack of automation and synchronization in the document process. The technologies used include free social networks, although it is noted that they are less effective for customer service than a virtual reception desk platform. The findings highlight the need for comprehensive digitalization and improvements in technological infrastructure, especially in rural areas, to optimize document management and user satisfaction. Future research on training and technical support is recommended to improve the implementation of digital services in the educational field and government policies that address inequalities in technological infrastructure.